Evidence for L1-associated DNA rearrangements and negligible L1 retrotransposition in glioblastoma multiforme. Issue 1 (December 2016) - Carreira, Patricia; Ewing, Adam; Li, Guibo; Schauer, Stephanie; Upton, Kyle; Fagg, Allister; Morell, Santiago; Kindlova, Michaela; Gerdes, Patricia; Richardson, Sandra; Li, Bo; Gerhardt, Daniel; et al.
Abstract Background LINE-1 (L1) retrotransposons are a notable endogenous source of mutagenesis in mammals. Notably, cancer cells can support unusual L1 retrotransposition and L1-associated sequence rearrangement mechanisms following DNA damage. Recent reports suggest that L1 is mobile in epithelial tumours and neural cells but, paradoxically, not in brain cancers. Results Here, using retrotransposon capture sequencing (RC-seq), we surveyed L1 mutations in 14 tumours classified as glioblastoma multiforme (GBM) or as a lower grade glioma. In four GBM tumours, we characterised one probable endonuclease-independent L1 insertion, two L1-associated rearrangements and one likelyAlu -Alu recombination event adjacent to an L1. These mutations included PCR validated intronic events in MeCP2 and EGFR. Despite sequencing L1 integration sites at up to 250× depth by RC-seq, we found no tumour-specific, endonuclease-dependent L1 insertions. Whole genome sequencing analysis of the tumours carrying the MeCP2 and EGFR L1 mutations also revealed no endonuclease-dependent L1 insertions. In a complementary in vitro assay, wild-type and endonuclease mutant L1 reporter constructs each mobilised very inefficiently in four cultured GBM cell lines. Conclusions These experiments altogether highlight the consistent absence of canonical L1 retrotransposition in GBM tumours and cultured cell lines, as well as atypical L1-associated sequence rearrangements following DNA damage in vivo.